(untitled) (Homoeopathy for All, 2025)
Psychological imbalances if they persist for a long time leave a deep impression on the body. This psyche spreads discord in the physical level and upsets the balance and functioning of the body. The relationship between the emotions and the digestion are established in Psychology and psychosomatic medicines. These harmful emotional effects are detrimental and may lead to psychosomatic diseases. English Physician Dr, Edward Bach (1886- 1936) realized that for the formation of chronic diseases, mind and emotions are responsible factors. He realized the different types of mental and emotional states which man experiences and tried to find the remedies which could address these emotions along with the imbalances. There are 38 Bach remedies. These remedies lift the emotions and thus prevent the development of the physical symptoms. If the physical symptoms appear then physical cure could be propelled. Bach healers. The study of the people in general, the clinical observation, the bacteriological study and the power stored in the plants together led to the invention of Bach Remedies. The lining and functioning of the bowel are the seat of individual reaction of the person along with the emotions. For e.g. the abdomen typically expresses grief by becoming numb and dead. Anxiety and nervousness are manifested by wrenching of the bowels and elimination increase.